Formation of plasmonic silver nanoparticles using rapid thermal annealing at low temperature and study in reflectance reduction of Si surface. (17th July 2017) - Barman, Bidyut; Dhasmana, Hrishikesh; Verma, Abhishek; Kumar, Amit; Chaudhary, Shiv Pratap; Jain, V K
Abstract: This work presents studies of plasmonic silver nanoparticles (AgNPs) formation at low temperatures (200 °C–300 °C) onto Si surface by sputtering followed with rapid thermal processing (RTP) for different time durations(5–30 min). The study reveals that 20 min RTP at all temperatures show minimum average size of AgNPs (60.42 nm) with corresponding reduction in reflectance of Si surface from 40.12% to mere 1.15% only in wavelength region 300–800 nm for RTP at 200 °C. A detailed supporting growth mechanism is also discussed. This low temperature technique can be helpful in achieving efficiency improvement in solar cells via reflectance reduction with additional features such as reproducibility, minimal time and very good adhesion without damaging underlying layers device parameters.